Audit of non-financial reporting: what standard should be used? - LUBENCHENKOО.; SHULHA, S. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2023)
A business entity of whatever kind seeks to operate in long-term perspective by achieving the strategies set out by it, including the strategies pertaining to social justice, environmental protection, friendly use of natural resources and their renewal. It is also a matter of the society’s concern. It is for this reason that non-financial reporting for sustainable development, provided by business entities, is demanded by users. The verification of non-financial information is assigned to independent auditors. Although auditors use the International Standard 3000 “Assurance Engagements Other Than Audits or Reviews of Historical Financial Information” for the verification purposes, the International Standard 3410 “Assurance Engagements on Greenhouse Gas Statements” can also be applied for specialized spheres. When non-financial information is submitted together with financial reporting, the International Standard 720 (revised) “The auditor’s responsibilities relating to other information” will be applicable. On the request of international donor organizations, an auditor is allowed to use the International Standard 4400 “Agreed-upon procedures engagements”. Given that the International Standard 3000 is the most demanded among the auditors, the International Auditing and Assurance Standards Board provided a guidance on its application. The phases of non-financial reporting audit and their content were clarifi ed on the basis of the International Standard 3000. The choice of an international standard depends on the conditions of an engagement and relies on the professional judgment of an auditor. Irrespective of a chosen standard, an auditor bears the responsibility for the assessment of published non-financial reports for sustainable development. Realizing the responsibility before users of non-financial reporting, an auditor must assure the quality of his services in keeping with the requirements of the International Standard on Quality Management (ISQM 1). The working document of an auditor “Quality assessment of assurance engagements other than audits or reviews of historical financial information (non-financial reporting)” was elaborated, which would help assure the internal control of auditing at engagement level. This document is standardized and can be used in the auditing practice.